2018
DOI: 10.1136/bmjopen-2017-020680
|View full text |Cite
|
Sign up to set email alerts
|

Association of common comorbidities with osteonecrosis: a nationwide population-based case–control study in Denmark

Abstract: ObjectiveTo examine recent time trends in the incidence of osteonecrosis (ON) in Denmark and to investigate different common comorbidities association with ON in a population-based setting.MethodsUsing Danish medical databases, we included all patients with a first-time hospital diagnosis of ON during 1995–2012. Each ON case was matched with 10 randomly selected population control subjects from general population. For all participants, we obtained a complete hospital history of comorbidities included in the Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
0
11
1
2
Order By: Relevance
“…The strongest risk factors for osteonecrosis were dialysis, osteomyelitis, hip fracture, and solid organ transplantation. Few previous studies have estimated the incidence of osteonecrosis in a general population, but two studies that did, one in Denmark and one in the UK, showed yearly rates of 1/10th or less than our study did [ 14 , 15 ]. Our cohort was older, but this difference cannot explain the entire difference because the UK study showed a considerably lower incidence in older adults as well [ 15 ].…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…The strongest risk factors for osteonecrosis were dialysis, osteomyelitis, hip fracture, and solid organ transplantation. Few previous studies have estimated the incidence of osteonecrosis in a general population, but two studies that did, one in Denmark and one in the UK, showed yearly rates of 1/10th or less than our study did [ 14 , 15 ]. Our cohort was older, but this difference cannot explain the entire difference because the UK study showed a considerably lower incidence in older adults as well [ 15 ].…”
Section: Discussioncontrasting
confidence: 81%
“…Our cohort was older, but this difference cannot explain the entire difference because the UK study showed a considerably lower incidence in older adults as well [ 15 ]. Possible explanations for the difference in incidence include geographic variation, a greater propensity of Swedish physicians to diagnose osteonecrosis, and a more complete coverage of specialist health care in the database we used to identify osteonecrosis, although the Danish study used a similar national database [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with osteonecrosis often need surgery and often suffer from pain, reduced mobility, and increased dependency . Recently, we reported that the incidence of osteonecrosis is about 10 times more common than previous studies have suggested, a finding that increases the clinical relevance of osteonecrosis. In the present study, the incidence of osteonecrosis of any site was 0.16% per year of exposure to BSD, although it was more than twice as high for patients taking zoledronic acid or denosumab.…”
Section: Discussionmentioning
confidence: 85%